2013
DOI: 10.1103/physrevlett.110.118701
|View full text |Cite
|
Sign up to set email alerts
|

Unfolding Accessibility Provides a Macroscopic Approach to Temporal Networks

Abstract: An accessibility graph of a network contains a link wherever there is a path of arbitrary length between two nodes. We generalize the concept of accessibility to temporal networks. Building an accessibility graph by consecutively adding paths of growing length (unfolding), we obtain information about the distribution of shortest path durations and characteristic time scales in temporal networks. Moreover, we define causal fidelity to measure the goodness of their static representation. The practicability of ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
94
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(97 citation statements)
references
References 27 publications
3
94
0
Order By: Relevance
“…Previous work has considered temporal and memory effects on spreading by modelling timerespecting paths in temporal networks of contacts 22,23,52 and bidirectional paths in mobility networks of commuters 27,28,53,54 . Our objective is to quantify the full effect of second-order Markov dynamics in general mobility patterns.…”
Section: First-order Markovmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work has considered temporal and memory effects on spreading by modelling timerespecting paths in temporal networks of contacts 22,23,52 and bidirectional paths in mobility networks of commuters 27,28,53,54 . Our objective is to quantify the full effect of second-order Markov dynamics in general mobility patterns.…”
Section: First-order Markovmentioning
confidence: 99%
“…Again, once random transmission occurs in a city, all memory effects are washed out in this metapopulation model. Therefore, the effect of a higher-order Markov process is primarily influential in the beginning of the outbreak during the introduction phase when the sequence of contacts matters 22,23,52 . Overall, we conclude that the first-and secondorder dynamics must be sufficiently different to show a clear difference on the spreading.…”
Section: First-order Markovmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, both the order and timing of interactions affect time-respecting paths-and thus causality-in temporal networks. Compared with the rich literature on node activities, a relatively smaller number of studies empirically investigated effects of causality in temporal networks 22,[24][25][26][27][28][29][30] . Recent works have shown that order correlations in temporal networks lead to causality structures, which significantly deviate from what is expected based on paths in the corresponding time-aggregated networks [27][28][29] .…”
mentioning
confidence: 99%
“…Compared with the rich literature on node activities, a relatively smaller number of studies empirically investigated effects of causality in temporal networks 22,[24][25][26][27][28][29][30] . Recent works have shown that order correlations in temporal networks lead to causality structures, which significantly deviate from what is expected based on paths in the corresponding time-aggregated networks [27][28][29] . Studying time-respecting paths a-b-c from the perspective of a contact sequence a,b,c passing through node b, it was shown that the next contact c not only depends on the current contact b but also on the previous one [28][29][30][31] .…”
mentioning
confidence: 99%